The Role of Health Management in Enhancing Community Health Center Service Quality under the National Health Insurance (JKN) Program in Coastal Areas - Aulia Purnama Rangkuti; Bulan Azahara Siregar; Dewi Agustina; Linda Jernih Hati Daeli; Nurhayati Telaumbanua (International Journal Of Health Science, 2025)
The implementation of the National Health Insurance (JKN) requires Community Health Centers (Puskesmas) as first-level health facilities to not only provide basic services but also optimize management governance to maintain service quality evenly, including in coastal areas that face geographical and social challenges. This study aims to analyze the role of health management in improving the quality of Community Health Center services in coastal areas during the JKN era through planning, organizing, implementing, and evaluating functions. The method used is descriptive qualitative with a phenomenological approach, through a literature review and analysis of the empirical experiences of Community Health Center managers, health workers, and the community. The results of the study indicate that the implementation of management functions has been carried out administratively, but its effectiveness still depends on human resource capacity, cross-sector support, and the ability to adapt to local cultural characteristics. Strategies that have proven effective include a proactive approach , digitalization of simple services, competency-based task allocation, and strengthening therapeutic communication. Structured health management has been shown to have a positive impact on accelerating services, increasing public trust, and reducing patient complaints. Thus, strengthening local needs-based management is key to the success of coastal Community Health Centers in supporting the implementation of JKN in an inclusive and equitable manner.